VIRTUE AND CATHOLIC SOCIAL TEACHING: A New Generation in an Ongoing Dialogue toward Greater Realization of Social Justice and the Common Good - O’Sullivan, James P (Asian Horizons, 2012)
What is the relationship between virtue and the vision of Catholic social teaching (CST)? This very broad question has been answered in different ways over the past several decades, and a new generation of scholars is moving the question forward. In this paper I will seek to show that there has been an evolution from the important, but insufficient, insertion of virtue into the discussion of CST to more nuanced and specific efforts of relating virtue to the vision in CST of social justice and the common good. In short, I hope to show that both the older and the newer approaches rightly insist that the vision of CST should be seen as calling for individual reform or ongoing conversion and that fostering virtues in individuals is an important part in realizing that vision. A new generation, however, has come to see the importance of fostering specific virtues and recognizes that the call to virtue and conversion does not replace the need for structural change (structural change cannot wait for a virtuous population). What is needed in this view is a balanced emphasis on both changing structures and fostering specific virtues, with the former importantly influencing the latter.